TREATMENT OF BOVINE SCHISTOSOMIASIS WITH MEDICINAL PLANT VERONIA ANTHELMINTICA (KALIZIRI), AN ALTERNATIVE APPROACH - Niaz, Sadaf; Akhtar, Tanveer; Shams, Sumaira; AbdEl-Salam, Naser M.; Ayaz, Sultan; Ullah, Riaz; Bibi, Safia; Hussain, Iqbal; Ahmad, Shabir (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Veronia anthelmintica (Kaliziri) is a medicinally very important plant as being reported for remarkable therapeutic potential. Thepresent research evaluates its antischistosomal activity.Methods and Materials: 54 buffaloes naturally infected with Schistosomiasis were used for anthelmintic trails. All animals for the study weretagged so as to distinguish from others. The animals were checked up on routine basis by a veterinary doctor. Preparation of samples of herbaldrug and experiment was design according to available literature.Results: During present studies, buffalos naturally infected with Schistosomiasis were treated with Veronia anthelmintica (Kaliziri), with dose75 mg/kg, 150 mg/kg and 225 mg/kg body weight respectively, and their impact on various parameters like eggs reduction, milk production,weight gain and feed intake was noted. Furthermore, their efficiency (%) was compared with standard drug “Praziquantel” (allopathic drug) at“10mg/Kg” body weight dose level. The effectiveness (%) of “Praziquantel” was noted as hundred after first dose, while the effectiveness for theherbal drug get to this level after injecting of second dose of “225mg/kg body weight”. Statistically significant (P<0.05 and P<0.001,respectively) increase in milk production was noted.Conclusion: Keeping in view of our present findings, it is concluded that herbal treatment of bovine schistosomiasis with Vernoniaanthelmintica (seeds) is safe, easy, readily applicable and cheapest method and almost have no side effect.